2023
DOI: 10.3389/fnsys.2023.1154014
|View full text |Cite
|
Sign up to set email alerts
|

Putting forward a model for the role of the cerebellum in cocaine-induced pavlovian memory

Abstract: Substance Use Disorder (SUD) involves emotional, cognitive, and motivational dysfunction. Long-lasting molecular and structural changes in brain regions functionally and anatomically linked to the cerebellum, such as the prefrontal cortex, amygdala, hippocampus, basal ganglia, and ventral tegmental area, are characteristic of SUD. Direct and indirect reciprocal connectivity between the cerebellum and these brain regions can explain cerebellar roles in Pavlovian and reinforcement learning, fear memory, and exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…These regions notably overlap with brain regions essential for fear-conditioned memory [ 134 ]. Golgi neurons are vital for the modulation of activity and plasticity in the cerebellum, and PNNs surrounding Golgi interneurons play a role in consolidating drug-related memories [ 135 ]. Fully condensed PNNs around Golgi interneurons can label synaptic alignments that represent drug-cue associations [ 135 ].…”
Section: Roles Of Pnns In Memory-related Dysfunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions notably overlap with brain regions essential for fear-conditioned memory [ 134 ]. Golgi neurons are vital for the modulation of activity and plasticity in the cerebellum, and PNNs surrounding Golgi interneurons play a role in consolidating drug-related memories [ 135 ]. Fully condensed PNNs around Golgi interneurons can label synaptic alignments that represent drug-cue associations [ 135 ].…”
Section: Roles Of Pnns In Memory-related Dysfunctionsmentioning
confidence: 99%
“…Golgi neurons are vital for the modulation of activity and plasticity in the cerebellum, and PNNs surrounding Golgi interneurons play a role in consolidating drug-related memories [ 135 ]. Fully condensed PNNs around Golgi interneurons can label synaptic alignments that represent drug-cue associations [ 135 ]. A recent study showed that cocaine-induced conditioned preference increased neural activity and upregulated PNNs around Golgi interneurons in the posterior cerebellar cortex.…”
Section: Roles Of Pnns In Memory-related Dysfunctionsmentioning
confidence: 99%